Beyond Limits: A Case of Progressive Leiomyosarcoma of the Mandible - Ordinario, Mel Valerie Cruz; Sabando, May; Panganiban, Anna Marie Pascual (Asian Pacific Journal of Cancer Care, 2023)
Leiomyosarcoma (LMS) is a rare malignancy which develops from the smooth muscles. It constitutes about 3 to 10% of all sarcomas in the head and neck area. Furthermore, it is extremely rare in the area of the mouth and jaws due to the rarity of smooth muscle in these areas. Spindle cells with visible smooth muscle differentiation, distinct features of atypia and presence of actin and desmin in Immunohistochemical (IHC) stains are characteristic of LMS. The common pattern of spread is similar with other sarcomas, involving the lung and rarely the lymphatics. Surgery, Radiotherapy and Chemotherapy have been described as standard forms of management. The prognosis is usually poor as rate of local, regional and distant metastasis is high. In this paper, we present a case of a 23 year-old female who presented with Leiomyosarcoma of the mandible. She remained to have good performance status and was able to undergo multiple lines of treatment for progressive disease prior to her demise.